Learning from jQuery - Macrae, Callum (Computer software developer) (O'Reilly, 2012)
If you're comfortable with jQuery but a bit shaky with JavaScript, this concise guide will help you expand your knowledge of the language--especially the code that jQuery covers up for you. Many jQuery devotees write as little code as possible, but with some JavaScript under your belt, you can prevent errors, reduce overhead, and make your application code more efficient. This book explores event handling, prototypes, and working with the DOM and AJAX through examples and lots of code. You'll learn common conventions and patterns in JavaScript and--if you've never coded with JavaScript before--a tutorial will take you through the basics. Enhance your jQuery code by using object constructors and prototypes Reduce overhead and gain more control by handling events with JavaScript Work with the DOM much faster with JavaScript than you can with jQuery Send a few AJAX requests without having to load the entire jQuery library Understand the importance of JavaScript code standards, comments, code reuse, and anti-patterns Enlist JavaScript resources, such as a good IDE, a syntax checker, and version control.